AI’S ROLE IN BUILDING A SOCIETY THAT RESPECTS FUNDAMENTAL RIGHTS. THE CASE STUDY OF THE TIKTOK BOLD GLAMOUR FILTER (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This article explores the role of Artificial Intelligence (AI) in building a society that respects fundamental rights, using TikTok's "Bold Glamour" filter as a case study. It analyses the ethical and social implications of AI-driven beauty filters, highlighting how they impact self-perception and reinforce unrealistic beauty standards. The research emphasises the need for a balanced approach in regulating AI, protecting consumer rights, and promoting ethical use. It discusses the European Commission guidelines and the importance of transparency, diversity, and non-discrimination in AI systems. The study concludes by proposing legislative, technological, and social interventions to mitigate potential harms.
Keywords: Artificial Intelligence; Ethical implications; Beauty filters; User vulnerability; Regulatory framework